How to Protect Future Generations' Rights in European Governance - Maja Göpel; Malte Arhelger (Intergenerational Justice Review)
Given that future generations are right-bearing citizens of tomorrow, legislative systems should secure these rights through appropriate institutions. In the case of the European Union, reference to intergenerational justice can be found in various fundamental legal texts, but, paradoxically, no institutions exist to defend it. The structural short-termism inscribed into representative democracies means that present interests easily trump future concerns. We argue that the best way to overcome this problem is a system of temporal checks and balances. By comparing a selection of existing instruments with regards to their impact on the legislative process, we propose the creation of a European Guardian for Future Generations as the most effective measure to protect the rights of future generations and provide an overview of recent developments in this direction.